Activating Schemata Helps Students in Reading Comprehension - Sholihatul Hamidah Daulay; Emeliya Sukma Dara Damanik; Rora Rizky Wandini; Eka Sagita (Edukasi, 2020)
Less of comprehension in reading of English text has become a problem to reach English mastery. This problem brings researchers to apply the activating schemata to solve student’s problem in MAS 22 Tembung Medan. In this research, the researcher took grade X as the population of the research. The population of the research is not too large. Then, the researchers decided to take the whole student as the sample of the research by using sampling technique. Researchers collected the data through pre-test and post-test during conducting of this research. After collecting of the data, the data is analyzed through SPSS 23.0 and tested by ANCOVA (an analysis of covariance) Finally, researcher found that activating schemata had a significant effect on student reading comprehension. It can be seen from the data resulted. The data shown that students in experimental group got score in the pre-test (70) and post-test (100). Meanwhile, students in control group got score pre-test (70) and post-test (70). Score of significance was 0.000 and it was lower than 0.05. Therefore, the hypothesis is accepted. This result concluded that activating schemata can increase student reading comprehension and the use of this strategy is recommended.